Relationship of Hypoalbuminemia in Colistin-Induced Acute Kidney Injury (AKI) among Adult Intensive Care Patients: Hypoalbuminemia in Colistin-Induced Acute Kidney Injury - Memon, Sughandh Umer; Samad, Saima; Misbah, Nazish; Muzaffar, Saima; Ishaque, Sadia; Kamran, Shumaila (Pakistan Journal of Health Sciences, 2025)
Acute kidney injury incidence ranges from 30-60% among critically ill patients and stands as the primary death cause within this population. A serious concern is a global rise in major drug-resistant-gram-negative organisms among hospital-acquired infections. Objectives: To determine the incidence of colistin-induced acute kidney injury in intensive care patients receiving colistin therapy and to investigate its relationship with albumin levels. Methods: It was a follow-up prospective cohort study executed at Shaheed Mohtarma Benazir Bhutto Institute of Trauma Pakistan in an adult intensive care unit over 6 months. The study end-point was an injury in intensive care injury at the end of colistin therapy. A total of 250 patients were studied. The median age of patients was 40 (IQR=22-48) years with an age range of 18-70 years. The majority of patients were male (75.2%). Median colistin dosage was 4 (IQR=3.5-4.5) MIU. In univariate analysis, the risk of developing injury in intensive care was significantly increased with increased age, use of nephrotoxic drugs, and increasing colistin dosage whereas injury in intensive care risk was decreased with increasing albumin levels. In a multivariable model, only colistin dosage was found to be significantly associated with increasing injury in intensive care risk with increasing colistin dosage. Conclusions: It was concluded that the present study analyzed a higher burden of acute kidney injury incidence following colistin therapy. Albumin levels were not found to be linked to acute kidney injury incidence in the multivariable model. Acute kidney injury incidence was significantly related to increasing colistin dosage.